Rawls’ Reflective Equilibrium as a Method of Justifying Moral Beliefs - Inusah, H.; Quansah, P.K. (Springer, 2021)
It is undeniable that people have beliefs about what actions are morally right. These beliefs play an important role in guiding moral action. Is it possible however to justify beliefs about what actions are morally right? How can beliefs of this sort be justified? Sinnott-Armstrong has advanced an epistemic regress argument against the justification of moral beliefs with the consequence that moral beliefs cannot be justified. This essay addresses the issue of the justification of moral beliefs to answer the question about how moral beliefs can be justified in response to Sinnott-Armstrong’s epistemic regress argument. It argues for the plausibility of Rawls’ reflective equilibrium as an adequate method of justification of moral beliefs. Three problems arise in the attempt to show that reflective equilibrium can adequately respond to Sinnott-Armstrong’s regress argument. These are vicious circularity, arbitrariness and epistemic moral disagreement. It is shown in this essay that these problems can be satisfactorily dealt with.
Research Article
Keywords: Reflective equilibrium; Justification; Moral disagreement; Vicious circularity